Decolorization of the Reactive Dyed Cotton Fabrics with the Use of Ozone Assisted Eco-technology (Journal of Fiber Bioengineering and Informatics, 2023)
The textile coloration sector normally employs the color stripping process for correcting the various faults obtained during the wet processing operations like the printing and dyeing. However, the traditional method for the color stripping carries with it the possibility of grave ecological pollution. The purpose of this work is to investigate the new, ecological method such as ozone based process for the color stripping of the reactive dyed textiles. This novel ozonation process was performed at room temperature with low amount of chemical auxiliaries. The effects of different process parameters like the acidic pH, 45 g/m3 ozone concentration and the treatment time of 30 minutes on the color stripping was investigated. Additional colorimetric analysis has been studied. The results indicate that the color stripping was achieved effectively at the atmospheric temperature with the ozonation process. This proposed technique was successfully implemented for the color stripping of different reactive dyes on the cotton substrate.